MOTIVASI DAN KOMUNIKASI ANTAR PETANI ANGGOTA KELOMPOK PISANG DI D.I. YOGYAKARTA - Riesma Andiani (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2022)
In Indonesia, banana is a horticulture commodity with the highest production number because it can be cultivated in various locations and does not depend on the season. Besides its high productivity, bananas are also very potential because they can be processed into various product. Unfortunately, the banana cultivation activity is vulnerable to some technical issues. In result, the productivity of banana might be loss. To be able to avoid losses, social approach towards the farmers is needed, not only come from the individual level but also requires cooperation among fellow banana farmers. This study was conducted to evaluate the motivation of the banana farmers and to analyze the communication among banana farmers in carrying out efforts to develop their banana cultivation. The method used were descriptive qualitative method and the data collected from the indepth interview to some banana farmer group leaders and producers of banana-processed food products in The Special Region of Yogyakarta. The results showed that the banana farmer keen to connect with many stakeholders related to their cultivation activities to help them develop their activities. The banana farm around their environment also encourages the farmers to develop tourism activity related to their cultivation activities. The farmers are able to maintain the good coordination and communication in developing the banana cultivation. All information is shared among all of the farmers, all group member can maintain their empathy and able to support each other. Therefore, they have a possitive communication and the responsibilities among them are equal.